The projection structure of microsomal glutathione transferase. - Hebert, H (1995)
Through the use of electron crystallography, it has been possible to obtain high resolution structural information regarding a mammalian protein that spans the lipid bilayer. Two-dimensional crystals of the detoxification enzyme microsomal glutathione transferase were induced by slow detergent removal from a mixture containing low amounts of phospholipid. Images of specimens stabilized in tannin were collected using electron cryomicroscopy. The projection structure at 4 A shows tightly packed trimers of the protein. Each of them contains an inner core of six parallel alpha-helices delineating a central low density region. The helical bundle is partly surrounded by elongated domains.